Confidential U.S. State Department Central Files. internal affairs, decimal number 883, and foreign affairs, decimal numbers 783 and 711.83 (University Publications of America, 1985)
Instructions sent to and correspondence received from diplomatic posts relating to Egypt's internal affairs, 1945-1949, including political affairs, public order, safety, health, and works, charities, military affairs, naval affairs, social, economic and industrial matters, communication and transportation, navigation, public press, and science; and foreign affairs, 1945-1949, including general and bilateral relations and U.S.-Egyptian relations.